DETERMINAN EFEKTIVITAS SISKEUDES DI KECAMATAN LANGSA LAMA - Sahlena; Muhammad Salman; Agustina Nurul Fajriah (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims to determine the influence of village government apparatus competency, information technology, and training on the effectiveness of the village financial system (Siskeudes) in villages in Langsa Lama District, Langsa City. This study used quantitative methods with primary data collected through questionnaires. The study population included all 15 villages in the district, using a saturated sampling technique, resulting in 60 respondents consisting of village heads, village secretaries, financial officers, and Siskeudes operators. Data analysis was conducted using SPSS through descriptive statistical analysis, data quality testing, classical assumption testing, multiple linear regression, and hypothesis testing. The results indicate that, both partially and simultaneously, apparatus competency, information technology, and training significantly influence the effectiveness of Siskeudes. This study's limitations lie in the limited number of variables studied, while many other factors can influence the effectiveness of the village financial system. The author recommends that further research expand the focus of the study and deepen the related literature to strengthen understanding of the research object.